Fixed-Bed Column Performance of NaOH-Activated Hybrid Adsorbent Derived from Jengkol Peels and Coconut Shells for Cu(II) Removal - Dwi Indah Lestari; Linda Ekawati; Syariful Maliki; Zeolita Prabu Putri; Isma Uly Maranggi (Science Education and Application Journal, 2026)
This study aims to evaluate the dynamic performance of NaOH-activated hybrid adsorbent derived from jengkol peels and coconut shell for Cu(II) removal in a fixed-bed column. The performance indicators include the adsorption capacity, removal efficiency, and structural characterization. The hybrid adsorbent was characterized using Fourier Transform Infrared Spectroscopy (FTIR) to identify functional groups that play a role in the adsorption process and Scanning Electron Microscope (SEM). The FTIR characterization results showed that the hybrid adsorbent was rich in functional groups such as hydroxyl (-OH), aromatic stretching (C=C), and aliphatic (C-H) groups. Meanwhile, the SEM characterization showed that the surface structure of the adsorbent tended to be honeycomb-shaped with varying pores. The adsorption test was performed in a downflow fixed-bed column under continuous operation with a total operation time of 30 minutes. Under the tested conditions (influent concentration of 100 mg/L and flow rate of 25 mL/min), 95% removal was achieved at 30 min in the fixed-bed column system, corresponding to a dynamic adsorption capacity of 11.3 mg/g. Kinetic modelling indicated that the Thomas and Yoon – Nelson models provided a better fit than the Adam-Bohart model, indicating that adsorption was primarily controlled by surface kinetics rather than intraparticle diffusion. This biomass waste-based hybrid adsorbent has the potential to be an environmentally friendly alternative for treating liquid waste containing Cu ions.